Imidacloprid induces adverse effects on fish early life stages that are more severe in Japanese medaka (Oryzias latipes) than in zebrafish (Danio rerio). (June 2019) - Vignet, Caroline; Cappello, Tiziana; Fu, Qiuguo; Lajoie, Kévin; De Marco, Giuseppe; Clérandeau, Christelle; Mottaz, Hélène; Maisano, Maria; Hollender, Juliane; Schirmer, Kristin; Cachot, Jérôme
Abstract: Neonicotinoids are widely used insecticides that have frequently been found in freshwater with concentrations ranging from ng to μg/L. It is known that these compounds impact non-target invertebrates, such as bees and gammaridae, in terms of toxicity and behavior, but impacts and species differences on vertebrates such as fish are little explored. The aim of this study was to investigate and compare the effects of one widely used neonicotinoid, imidacloprid, on development and behavior of two fish model species: Zebrafish ( Danio rerio ) and Japanese medaka ( Oryzias latipes ). Fish were exposed for 5 (zebrafish) and 14 (medaka) days from 0.2 to 2000 μg/L imidacloprid by aqueous exposure. Survival, development, behavior and histological features were monitored and organism-internal concentrations and biotransformation products measured. Imidacloprid caused sublethal effects in both species but the effects were much stronger in medaka with deformities, lesions and reduced growth being the most prominent impacts. Due to the overall longer time of development, time-integrated exposure of medaka was about 2-fold higher compared to zebrafish, potentially accounting for parts of the sensitivity differences. Our results underline the importance of taking species sensitivity differences into account especially when considering that medaka responded at imidacloprid concentrations that have been measured in the environment. Graphical abstract: Image 1 Highlights: Imidacloprid impacts on fish at environmentally relevant concentrations. At the same developmental stage, medaka are more sensitive than zebrafish. Our study supports the importance of taking species sensitivity differences into account.